Towards a New Critical Edition of Yavuz Sultān Selīm’s Persian Dīvān: An Overview of The Manuscripts - Benedek Péri (Akademik Dil ve Edebiyat Dergisi, 2026)
Many Ottoman Sultans excelled in poetry but Selīm I was the only one who composed poetry almost exclusively in Persian. The first printed edition of the divan was published in Istanbul in 1889. This edition was based on a single manuscript. The first critical edition was prepared by a German Iranist, Paul Horn in 1904. He based his work on seven manuscripts four of which he found in European libraries. Only three came from libraries in Turkey. A couple of years ago a project was started to prepare a new edition of the divan. The work started with browsing library catalogues and collecting manuscripts that were unknown to Horn. The search included libraries in Europe and the Middle East. Many new manuscripts were found. The new critical edition that is planned to be printed this year is going to be based on Horn’s edition and 24 manuscripts 21 of which were not seen by Horn. Nineteen of the manuscripts are from libraries in Turkey, four are from libraries in Tehran and one is from Israel. These manuscript contained many unpublished poems. The aim of the present article is to give a detailed description of all the manuscripts used for the new critical edition of Sultān Selīm’s divan.